2020
DOI: 10.1101/2020.09.25.20201343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Onset, duration, and persistence of taste and smell changes and other COVID-19 symptoms: longitudinal study in Israeli patients

Abstract: Objectives: The multifaceted disease manifestation of COVID-19 requires longitudinal characterization of symptoms, to aid with screening and disease management. Methods: Phone interviews and follow-ups were completed with 112 mild COVID-19 RT-PCR-positive adult patients, over a 6 week period. Results: More than one symptom at disease onset was experienced by ~70 of the patients. Over one third of patients experienced fever, dry cough, headache, or muscle ache as the first symptom. If fatigue was reported, it … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In children, the result was not statistically significant, possibly due to a small sample size. Although anosmia and ageusia were initially less described as COVID-19 symptoms 3,6 , and were not part of the Israeli testing policy throughout the study period, they further emerged as the most predictive symptoms for COVID-19 in this study and others 10,12,22 , and were also found to be the most prolong symptoms in infected individuals 23 . Health organizations worldwide have gradually added it to the list of COVID-19 related symptoms including the USA CDC 24 , the UK 25 and Israel 26 .…”
Section: Discussionmentioning
confidence: 52%
“…In children, the result was not statistically significant, possibly due to a small sample size. Although anosmia and ageusia were initially less described as COVID-19 symptoms 3,6 , and were not part of the Israeli testing policy throughout the study period, they further emerged as the most predictive symptoms for COVID-19 in this study and others 10,12,22 , and were also found to be the most prolong symptoms in infected individuals 23 . Health organizations worldwide have gradually added it to the list of COVID-19 related symptoms including the USA CDC 24 , the UK 25 and Israel 26 .…”
Section: Discussionmentioning
confidence: 52%
“…In a study of European multiple sites, 9.4% of patients reported gustatory dysfunction after a mean follow-up of 63 days from the first consultation [ 96 ]. A longitudinal study showed that taste alteration of Israeli patients lasts long with the mean duration of 17.2 days [ 113 ]. Boscolo-Rizzo et al [ 144 ] followed up symptoms of mildly symptomatic COVID-19 patients from baseline to four and eight weeks.…”
Section: Gustatory Dysfunctionmentioning
confidence: 99%
“…Available literature supports spontaneous improvement with a mean duration of 2-3 weeks [23,24]. However, cases with symptoms lasting more than 1 month, so called persistent anosmia, have also been reported [25][26][27]. Considering the fact that olfactory epithelium undergoes regeneration over 6-8 weeks, SARS-COV2 may result in anosmia longer than 2-3 weeks due to the epithelia damage caused [28].…”
Section: Clinical Features Of Covid-19 Anosmiamentioning
confidence: 99%